Uncommon diagnosis of an emphysematous cystitis - Seifert, Dana; Jaganjac, Suad M (Scripta Medica, 2019)
A case of a 79-year-old woman who developed emphysematous cystitis (EC) prior to scheduled lower back surgery suffering from severe back pain was presented. She had neither of the known EC risk factors (diabetes mellitus, immunodeficiency, neurogenic bladder and recurrent urinary tract infections) and presented herself without classical signs of EC (dysuria, haematuria, abdominal pain, pollakiuria, pneumaturia). She had a persistent back pain that was masked by her chronic back condition, leucocytosis and increased C-reactive protein (CRP) concentrations. The abdominal ultrasound showed a suspiciously impeded, cloudy vision in the lower pelvis and a blurry, thickened presentation of the wall of the urinary bladder with high echogenicity. A CT scan of the abdomen was performed and confirmed the diagnosis of an emphysematous cystitis, as well as a secondary pyelonephritis Escherichia coli was isolated from urine and blood and successfully treated with ciprofloxacin. Contrast-enhanced CT imaging is the diagnostic method of choice.